Local ports and consumer goods: Import of fine goods in Santander, Colombia, 1870-1900 - Carreño Tarazona, Clara Inés [UNESP] (Instituto de Investigaciones Dr. Jose Maria Luis Mora, 2015)
This article analyzes the import of consumer goods, social environment and the local ports, as elements that formed part of the merchant circuit in Santander, Colombia, between 1870 and 1900. First, examines the commercial movement between major foreign ports and the local Colombian ports. In second place are studied various forms of association adopted by the leading importers to venture into foreign trade. Finally, listed goods and luxury goods, introduced by these importers, and their incorporation into the various social groups are indicated. Employed sources are notarial protocols, consulates and customs records, judicial funds, the departmental Gazettes and official newspapers.
Puertos locales y bienes de consumo: Importación de mercancias finas en Santander, Colombia, 1870-1900
Keywords: Import; Merchant circuit; Merchant houses; Ports